The efficiency of the application of the heap lists to the algorithm of mesh generation - Kucwaj, J. (Computer Assisted Methods in Engineering and Science, 2010)
The paper presents an analysis of the efficiency of the application of heap lists data structures to the 2D triangular mesh generation algorithms. Such efficiency is especially important for the frontal methods for which the size of the generated mesh is controlled by a prescribed function in the considered domain. In the presented approach two advancing front procedures are presented: first for points insertion and the second for the Delaunay triangulation. If the heap lists are applied to the minimal size of frontal segment selection, a better quality mesh is obtained.